Maternal Microbiota Transfer Programs Offspring Eating Behavior - Pocheron, Anne-Lise; Le Dréan, Gwenola; Billard, Helene; Moyon, Thomas; Pagniez, Anthony; Heberden, Christine; Le Chatelier, Emmanuelle; Darmaun, Dominique; Michel, Catherine; Parnet, Patricia (Frontiers in Microbiology, 2021)
We investigated the potential role of maternal microbiota transfer from mother to child in programming the eating behavior of the offspring. Selectively bred Obese Prone (OP)/Obese Resistant (OR) Sprague Dawley dams were used since that strain is known to exhibit differences in the caecal microbiota and its metabolic capacity. Microbiota collected from the feces, vagina and milk of Obese-Prone (OP) / Obese-Resistant (OR) dams were transferred to conventional Fischer F344 recipient pups from birth to 15 days of age to create 3 groups of pups : F-OP, F-OR, and F-Sham group (that received the vehicle). We first analyzed the various microbiotas from donors and recipients at different sampling times. We then characterized the growth and eating behavior of the three groups of rats, from birth to adulthood, by measuring their caloric intake, their anticipatory food reward responses, the taste perception or gustation during ingestion of sweet and fat solution and the sensations that extend after food ingestion. We then search for correlation between microbiota composition and food intake parameters. We found that maternal transfer of microbiota differing in composition led to alterations in pups gut microbiota composition that did not last until adulthood but were associated with specific eating behavior characteristics that were predisposing F-OP rats to higher risk of over consuming at subsequent periods of their life. These findings support the view that neonatal gut microbiotal transfer can program eating behavior, even without a significant long lasting impact on adulthood microbiota composition.